Molecular Detection and Risk Factors of Toxoplasma gondii among Aborted Women in Diyala / Iraq - Darweesh, Nariman Hassan; Hussein, Rawaa A.; Salman, Sawsan Talib; Shaker, Mohammed Jasim (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Background: Toxoplasma gondii is an obligate intracellular protozoan, that has the capacity to infect human and all warm blooded animals. Maternal infection with toxoplasmosis during gestation and its transmission to the fetus continue to be the cause of tragic yet preventable disease in offspring. Objectives: The present study is designed to determine the infection rate of T. gondii in two groups of aborted women (non-pregnant and pregnant), to evaluate the most effective methods in detection of toxoplasmosis and to investigate the relationship between T. gondii infection and some of the demographic characteristics. Methods: One hundred fifty women were included in this study to detect anti- Toxoplasma antibodies. The study included one hundred women divided in 2 groups; group 1: Include 58 sponteneous aborted women, group 2: Include 42 pregnant women with previous sponteneous abortion and 50 women with close ages who had no abortion or pregnancy were considered as a control group. All were attend to Al-Batool Teaching Hospital in Baqubah city/ Diyala province, during the period from 2016 till 2017. Their age ranged between (14 - 55) years. A questionnaire on personal information was prepared, asked them about different socio-demographic data. The presented study included serological and molecular examinations, toxoplasmosis diagnosed serologically by enzyme linked immunosorbent assay (ELISA) test for (IgM and IgG antibodies), IgG avidity-assay, in addition to the Real time polymerase chain reaction (RT-PCR) were used in an attempt to diagnose toxoplasmosis in the blood of abortive non pregnant and pregnant women. Results: This study showed that 44(44%) were positive by ELISA (IgG and IgM) which considered as a confirmed toxoplasmosis cases, 4 (4%) of abortive women had IgM+, 38 (38%) had IgG+, and 2(2%) had both IgM+ and IgG+, whereas the control women were 0% for all types of antibodies. The highest results of these tests were observed in 25-34 years age, 70.5% of women with positive results were aborted at the first trimester, 47.7% of these women with single abortion and 56.8% haven't children. The present study demonstrated a significant relation between non pregnant and pregnant women for IgG, the majority of IgG positive cases were observed in non-pregnant group. Also there was a relationship between increased the seropositive of aborted women for anti-T. gondii in housewives women and illiterate or in complete primary school, residence in rural area, and contact with animals. Real-Time PCR test in blood of pregnant and non-pregnant women has advantages in detection of recent or active toxoplasmosis, 15/100 (15%) of aborted women were positive by RT-PCR for toxoplasmosis associated with low avidity IgG, 4 of abortive women with IgM+ were RT-PCR positive. In addition, 7 of abortive women with IgG+, 2 of abortive women with IgM+& IgG+ were RT-PCR positive. Although 2 cases of abortive women with IgM-& IgG- were RT-PCR positive. A point to be noted in this study, is the presence of 9 cases which were IgM negative by ELISA test but were positive by RT- PCR. Conclusion: The results of the present study indicate that the most effective method in detection of the infection of T. gondii is RT- PCR in addition to avidity IgG method to give a real perception of the disease.